Health study of 11,800 workers under occupational noise in Xinjiang - Shiyu Zhao; Dongkui He; Hanwei Zhang; Tingting Hou; Chengxin Yang; Wen Ding; Ping He (BMC, 2021)
Abstract Background We investigated the health status of some workers exposed to occupational noise in Xinjiang, and explored the influencing factors of their health level. We aimed to determine the key protection groups of occupational noise hazards, which might provide the basis for the development of targeted noise prevention measures. Methods We used descriptive analysis to investigate a total of 11,800 participants who underwent occupational health examination in Xinjiang Occupational Disease Prevention Hospital. Results The hearing abnormality rate of noise exposure participants was 8.03%, which was higher in males than females (χ2 = 54.507, p < 0.05). The abnormal rate of high-frequency hearing threshold in Xinjiang minorities was lower than in Han nationality (χ2 = 11.780, p < 0.05), while the results of the electrocardiogram were reversed (χ2 = 9.128, p < 0.05). Differences in abnormal rates of blood pressure (χ2 = 149.734, p < 0.05), hearing (χ2 = 231.203, p < 0.05), and physical examination (χ2 = 360.609, p < 0.05) are statistically significant in different industries. The abnormal rates of blood pressure (χ2 = 67.416, p < 0.05) and hearing (χ2 = 49.535, p < 0.05) gradually decrease with the expansion of the enterprise scale. Logistic regression analysis showed that gender, nationality, age, enterprise size, and industry were closely related to pure tone audiometry examination abnormal rate. Conclusion Workers of male, elder, in mine and small/medium enterprises should be the key populations to prevent occupational noise hazard. It is necessary to standardize occupational health management in enterprises, which helps to improve workers' self-protection awareness and quality of life.